Evaluation of fatigue in sport performance - Rouard, A.; Aujouannet, Y.; Zory, R.; Bonifazi, M.; Schena, F. (International Congress Mountain & Sport. Updating study and research from laboratory to field. 11th-12th November 2005. Rovereto (TN) - Italy. Programme and book of abstracts, 2005)
Introduction: Fatigue is a complex process affecting the movement production either at the central level (i.e. nervous system) and/or peripheral level (i.e. muscle), (Enoka et Stuart, 1992). Biomechanical aspects of fatigue on elementary movements indicated a decrease in force production associated to changes in EMG depending of the type of exercise (De Luca, 1997). Modifications in co-activation were observed indicating changes in the control of the movement (Kellis et al, 2001). Few studies focused on the effects of fatigue in cyclic sports such as swimming and cross-country skiing. During competitions or tests conditions, a decrease of velocity relating to the decreases of cycle rate and cycle length were observed both in swimming (Craig et al, 1979) and cross-country skiing (Bilodeau et al, 1996). Even CV and CL resulted from forces production and muscular activations, few studies focused on the effects of fatigue on biomechanical parameters. In regard to the previous studies on elementary movements, the main gaols of our team research, for more than 20years, were to 1-characterise the influence of fatigue on biomechanical parameters in complex cycling motions,2 -to identify the sites of fatigue (central and/or peripheral),3-to analyse the individual biomechanical adaptations to fatigue. Methods: Different studies were realised with top level athletes. Tests reproduced different races conditions to conduct the athletes up to exhaustion. They ranged from controlled elementary movements to complex non controlled movements. The kinematic data were collected with front and side videos and digitised with KA video software (Schleihauf). EMG`s were collected on agonist-antagonist muscles with an 8 channels system (ME 3000 P8, Mega Electronics Ltd, Finland) and treated with Megawin software IEMG and RMS and time-frequency treatment (Knaflitz et Bonato, 1999). The forces were measured with self-developed ergometers (INSA, Lyon for swimming, and CeBism for cross country) to obtain force, power of the limbs before and after the exhaustive test. Results: One of the swimming studies concerned the influence of lactates production on stroke parameters and muscular upper limb recruitments in 3 different training exercises (5*200m - 7*100m - 2* (4*50m) separated by active recovery). Results on national French swimmers indicated an increase of muscular recruitments for all the tests with different increments from one repetition to another reflecting different muscular efforts from one test to another An other study on a 400m exhaustive test realised in the flume with national American swimmers indicated a decrease in hand forces and a delay of forces production from the central to the final phases of the cycle with fatigue. The last study realised with the Italian swimming team, consisted in 4*50m at maximal velocity with a 10s rest. Results indicated a decrease of all the forces after the test. Temporal hand pattern increased when spatial parameters remained unchanged under fatigue. Greater recruitments and co-activations moved from the central part to the end of the cycle. Decrease of frequency was observed for the antagonist muscles of the wrist throughout the 4*50m. First data obtained after a KO sprint simulation were closed to swimming results. Furthermore, the comparison of force and EMG obtained in evoked and voluntary contractions suggested mainly a peripheral fatigue. For all these studies great individual variations were observed among subjects. Conclusion: The effects of exhaustive tests on physiological, mechanical, kinematic and EMG parameters in cycling complex movements were similar to the effects of fatigue observed in isometric conditions.. Furthermore, the results suggested mainly a peripheral fatigue. Great individual variations were observed for all biomechanical parameters suggesting the individualisation of training exercises among top-level athletes.